Selecting and tailoring design methodologies in form of roadmaps for a specific development project - Nieberding, Friedrich Hagen Martin (Stellenbosch : University of Stellenbosch, 2010)
Thesis (DEng (Industrial Engineering))--University of Stellenbosch, 2010.